Personalized dietary advices provided by a dietitian increase calcium intake in outpatients with multiple sclerosis—Results from a randomized, controlled, single-blind trial - Fiorella, Sandrine; Agherbi, Hanane; El Houjeiry, Emilia; Castelnovo, Giovanni; Renard, Dimitri; Privat, Pauline; Santamaria, Elodie; Vallayer, Virginie; Alonso, Sandrine; Chevallier, Thierry; Bancal, Candice; Laurent-Chabalier, Sabine; et al. (Frontiers in Nutrition, 2023)
Background & Aims: Multiple sclerosis (MS) is associated with osteoporosis, possibly due to neurological disability and decreased calcium intake. The objective of this study was to evaluate the efficacy of a personalized nutritional advice program by a dietitian compared to the delivery of a standard advice form to optimize dietary calcium intake in outpatients with MS. Methods: We performed a randomized, controlled, parallel trial comparing the efficacy of a personalized dietary advice (PDA) program to standard advice form (SAF) to increase daily calcium intake in MS patients. The study population was composed by patients with relapsing-remitting MS aged 18-69 years old. PDA program consisted in dietary advice delivered by a dietitian at baseline, 1 month, and 3 months. Calcium and nutrient intake in patients from both groups was evaluated at baseline and 6 months using a dietary survey. Results: Of the 194 patients screened for inclusion, 182 patients were included (79% female, median age of 42 years, and median EDSS of 2.0), and randomized to SAF (n=92) or PDA (n=90). At 6 months, median calcium intake increased by 241 mg/d in the PDA group and decreased by 120 mg/d in the SAF group (p<0.0001). However, the median calcium intake was 947 mg/d in the SAF group and 778 mg/d in the PDA group at baseline (p=0.0077), potentially favoring the effect of dietary advice. Complementary analyses focusing on patients with insufficient calcium intakes at baseline revealed comparable values in both groups (p=0.69). Of those, patients included in the PDA group obtained significantly higher calcium intakes at 6 months than patients from the SAF group (p=0.0086) independently of EDSS, PASAT, HADS and EQ-5D scores. Conclusions: This work shows the efficacy of dietary management based on personalized advice program over 3 months to durably increase calcium consumption in MS patients with insufficient calcium intake.